2018
DOI: 10.1001/jamainternmed.2018.3629
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a Mailed Colorectal Cancer Screening Outreach Program in Community Health Clinics

Abstract: IMPORTANCE Approximately 24 million US individuals receive care at federally qualified health centers, which historically have low rates of colorectal cancer screening. The US Preventive Services Task Force recommends routine colorectal cancer screening for individuals aged 50 to 75 years. OBJECTIVE To determine the effectiveness of an electronic health record (EHR)-embedded mailed fecal immunochemical test (FIT) outreach program implemented in health centers as part of standard care. DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 24 publications
5
111
1
1
Order By: Relevance
“…The current study data concerning follow‐up colonoscopy completion rates (33% to 36%) indicated room for improvement in both health plans. Low participation in follow‐up colonoscopy is a recognized limitation of FIT‐based programs, and the rates observed herein were even lower than the 52% to 53% found in previous research involving health centers serving the Medicaid population . In Health Plan Washington, this finding may have been attributable to low reach (60.0%) of the care coordinator telephone calls and/or the care coordinators' inability to directly inform patients of their test results.…”
Section: Discussioncontrasting
confidence: 72%
“…The current study data concerning follow‐up colonoscopy completion rates (33% to 36%) indicated room for improvement in both health plans. Low participation in follow‐up colonoscopy is a recognized limitation of FIT‐based programs, and the rates observed herein were even lower than the 52% to 53% found in previous research involving health centers serving the Medicaid population . In Health Plan Washington, this finding may have been attributable to low reach (60.0%) of the care coordinator telephone calls and/or the care coordinators' inability to directly inform patients of their test results.…”
Section: Discussioncontrasting
confidence: 72%
“…This research demonstrates the feasibility of implementing mailed FIT programs tailored to health plans based on their resources and preferences, as well as the substantial successes and addressable challenges that health plans experience as they work to lower rates of CRC and cancer death among their members. The two health plans participating in this study successfully adapted the components of prior clinic-and health system-based mailed FIT programs [4,6,8] to their own culture and resources, and found that their programs were a good fit with their organizational mission and goals. The availability of quality management resources allowed the health plans to overcome the most commonly described challenges reported for clinic-and health system-based mailed FIT programs-the time needed to set up and administer the program.…”
Section: Resultsmentioning
confidence: 99%
“…Mailing fecal immunochemical test (FIT) kits to patients who are due for CRC screening is an evidence-based strategy for increasing CRC screening that has been tested by clinics and health care systems [4][5][6][7][8][9] (e.g., CRC screening rates have increased from 26.3 to 50.8% in primary care clinics in a large nonprofit health care delivery system [8], from 17.8 to 56.5% in rural family physician offices [9]). Health insurance plans are now beginning to implement mailed FIT screening programs [10].…”
Section: Introductionmentioning
confidence: 99%
“…These outreach events, which formed partnerships with community healthcare systems to care for underserved groups, were implemented from 2010 to 2012, and about 81% of attendees received colorectal cancer screenings [15]. Meanwhile, an outreach program providing mailing service for fecal occult blood test kits has also been reported to be an effective strategy for increasing of colorectal cancer screening uptake [16,17]. The Helping Her Live project, which seeks to improve breast screenings and follow-ups for abnormal breast screening findings, has been implemented among minority women experiencing racial disparities in Chicago since 2008.…”
Section: For Increasing Health Screening Compliancementioning
confidence: 99%